THE RELATIONSHIP ADMINISTRATOR’S COMPETENCY WITH TEACHER’S PERFORMANCE IN THE SCHOOLS OF CHIANG RAI PRIMARY EDUCATIONAL SERVICE AREA OFFICE 1 - Kaewpratoom, Arisa; Chancharoen, Jintana; Tangkawanich , Thitiarpha (Journal of MCU Nakhondhat, 2023)
The purposes of this research were 1)The administrator’s competencies 2) Teacher’s performance 3)The relationship between administrator’s competency and teacher’s performance in the schools of Chiang rai primary educational service area office 1 , the thesis is Quantitative Research, the samples were 82 in the schools of Chiang rai primary educational service area office 1 the respondents of each school were a manager or a school director, a deputy school director and teachers totally 305 respondents the research instrument was a questionnaire concerning administrator’s competency in the Schools of Chiang rai primary educational service area office 1 based on the theory of Boyatzis (1996) have 6 topics were knowledge ,Human Resource, management, leadership, command, and maturity. Teacher’s performance in the Schools of Chiang rai primary educational service area office 1 have 12 topics according to professional standards for teachers based on the regulations of the teachers council of Thailand on professional standards b.e. 2013 the statistics for analyzing the data were frequency, percentage, arithmetic mean, standard deviation and pearson’s product moment correlation coefficient the findings were as follows 1) Administrator’s competency in the schools of Chiang rai primary educational service area office 1, collectively was found at a high level. 2) Teacher’s performance in the schools of Chiang rai primary educational service area office 1, collectively was found at a high level. 3) The relationship between administrator’s competency and teacher’s performance in the schools of Chiang rai primary educational service area office 1 was found at (r = .616, p < .001)